PENGARUH MEDIA SOSIAL TERHADAP SIKAP KEBERAGAMAAN PESERTA DIDIK - Anisa; Anjclan Jafar; Andi Nurfadilah; Ahmad Wildan; Nur Arrum; Muhamaad Farhan; Sabrun Jamil (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The rapid development of social media has influenced various aspects of life, including students’ attitudes toward diversity. Social media is not only a means of communication and information but also a space for interaction that can shape students’ perspectives on differences in ethnicity, religion, culture, and social views. This study aims to examine the influence of social media on students’ attitudes toward diversity. The research methodology employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to students selected using purposive sampling techniques. Data analysis was conducted using descriptive and inferential statistical methods to determine the relationship and influence between the intensity of social media use and students’ attitudes toward diversity. The results indicate that social media has a significant influence on students’ attitudes toward diversity. Students who use social media positively and critically tend to demonstrate tolerance, mutual respect, and openness toward differences. Conversely, the use of social media without adequate guidance and digital literacy may lead to intolerant attitudes and negative prejudices. Therefore, the role of teachers and parents is essential in guiding students to use social media wisely in order to strengthen attitudes of diversity within the educational environment.